(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
Faecal calprotectin (FC) is supposed to be a reliable biomarker that quantifies intestinal inflammation in inflammatory bowel disease (IBD). This cross sectional study was aimed to determine the role of FC level in screening of suspected IBD patients and monitoring treatment response. This study was conducted by measurement of FC using a commercially available ELISA kit among 50 patients with chronic diarrhea who underwent colonoscopic evaluation (25 IBD cases, 10 other organic bowel diseases and 15 disease control) and 12 healthy control. IBD patients were followed up after one month of medical treatment. FC level showed significantly higher value (p<0.001) among IBD patients (496.7±127.15?g/g) than those in disease control (82.17±75.64?g/g) and healthy control (27±18.2?g/g). Measurement of FC in diagnosing IBD revealed the sensitivity 100%, specificity 66%, PPV 83% and NPV 100%. The FC level decreased significantly (p<0.001) after one month of medical treatment of IBD patients (90±43?g/g) from pre treatment value (607.56±94?g/g). FC can be used as a reliable biomarker in screening of suspected IBD patients and to monitor treatment response. Bangladesh J Med Microbiol 2014; 08 (01): 12-15